Computational Intelligence Paradigms in Economic and Financial Decision Making - Resta, Marina; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The book focuses on a set of cutting-edge research techniques, highlighting the potential of soft computing tools in the analysis of economic and financial phenomena and in providing support for the decision-making process. In the first part the textbook presents a comprehensive and self-contained introduction to the field of self-organizing maps, elastic maps and social network analysis tools and provides necessary background material on the topic, including a discussion of more recent developments in the field. In the second part the focus is on practical applications, with particular attention paid to budgeting problems, market simulations, and decision-making processes, and on how such problems can be effectively managed by developing proper methods to automatically detect certain patterns. The book offers a valuable resource for both students and practitioners with an introductory-level college math background.
Keywords: Computational intelligence; Artificial intelligence; Operations research; Computational Intelligence; Artificial Intelligence; Operations Research and Decision Theory